2000
DOI: 10.1034/j.1600-051x.2000.027001009.x
|View full text |Cite
|
Sign up to set email alerts
|

Stain, plaque and gingivitis reduction by combining chlorhexidine and peroxyborate

Abstract: In conclusion, the adjunctive use of an oxidising agent peroxyborate to chlorhexidine, proved to be superior to chlorhexidine alone with regard to the inhibition of plaque and development of gingivitis. In addition, the proportion of stained surfaces was significantly less when adding the oxidising mouthrinse to chlorhexidine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
108
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(122 citation statements)
references
References 24 publications
5
108
1
3
Order By: Relevance
“…The present study results also demonstrated that Group 3 (involving the individual use of mouthwash) was also found to be effective in reducing the mean plaque scores from baseline to each time interval. This finding is in agreement with the previous studies by Grundemann et al [23], Francetti et al [24] and Waghmere et al [25]. This may be due to the property of substantivity and anti-plaque property of Chlorhexidine which suggest that individual use of Chemical oral hygiene aids i.e.…”
Section: Discussionsupporting
confidence: 93%
“…The present study results also demonstrated that Group 3 (involving the individual use of mouthwash) was also found to be effective in reducing the mean plaque scores from baseline to each time interval. This finding is in agreement with the previous studies by Grundemann et al [23], Francetti et al [24] and Waghmere et al [25]. This may be due to the property of substantivity and anti-plaque property of Chlorhexidine which suggest that individual use of Chemical oral hygiene aids i.e.…”
Section: Discussionsupporting
confidence: 93%
“…Clinical trials utilizing experimental gingivitis models have been frequently used as a short-term model to evaluate the antiplaque and antigingivitis efficacy of mouthrinses containing antimicrobial agents. These trials have tested a fixed combination of essential oils, 8,9 0.12% chlorhexidine gluconate, 25,26 cetylpyridinium chloride, 27 0.1% hexetidine, 28 and other noncommercial antimicrobial agents. 29 Therefore, there is enough evidence to support that experimental gingivitis study designs, like long-term models, have been accepted as a valid model to determine and compare efficacy of antiseptic mouthrinses.…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic is the basis for their use as bleaching agents in detergents, cleaning products and cosmetic preparations, as well as a preservative in eye drops (Safety, 2010). In clinical dentistry, boron-derived compounds are used as a bleaching agent for teeth and as an adjunct to CHX to counteract extrinsic staining of the tongue and tooth surfaces (Dona et al, 1998; Grundemann et al, 2000; van Maanen-Schakel et al, 2012; Feiz et al, 2014). …”
Section: Introductionmentioning
confidence: 99%